APPLICATION OF THERMAL CALCULATION PROGRAM TO CHECK THE OPERATION OF A MOTOR PERKINS DIESEL MODEL C4.236.V - COMPARATIVE ANALYSIS BY GASODIESEL - Maza Rubina, Arturo (2014)
This research was conducted in Lima and is on the development and implementation of a program based on thermal calculation; to determine the operating parameters of an internal combustion engine for automotive use, by simulating various processes occurring in engines, which allow to establish the expected rate of the operating cycle of an internal combustion engine of gasodiesel type (GLP + D2). The development of the thermal calculation, based on the behavior of the engine working as gasodiesel, is validated and contrasted with the experimental values, through a comparative analysis of the characteristics of the diesel engine Perkins, obtained in the test Newage and simulated characteristics of the engine; by the computer program AJESA 2004, finally each sub-hypothesis is tested and this allows us to formulate conclusions.